Implementation of Islamic Values-Based Deep Learning Approach in Natural and Social Science Learning in Elementary Schools - Siti Mahmudah; Raya Mangsi; H. M. Nasir S; Muhammad Naim (EDUJAVARE: International Journal of Educational Research, 2026)
This study is grounded in the importance of implementing a deep learning approach within the Merdeka Curriculum, which emphasizes not only conceptual mastery but also character formation, spiritual awareness, and meaningful learning experiences, particularly in Natural and Social Sciences (IPAS) instruction at the elementary level. This study aims to describe the planning, implementation, and evaluation of IPAS learning through a deep learning approach grounded in Islamic values, to analyze the forms and processes of integrating Islamic values into that learning, and to examine its impact on students' learning experiences, conceptual understanding, and Islamic character formation at SDN 003 North Bontang. A qualitative case-study approach was employed. Data were gathered through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana comprising data condensation, data display, and conclusion drawing, with validity established through source, technique, and time triangulation as well as member checking. The findings show that deep learning was implemented systematically through the preparation of Deep Learning Lesson Plans (RPPM), the application of Problem Based Learning and Inquiry/Discovery Learning strategies, and meaningful reflection grounded in Islamic values; the integration of tawhid and akhlak values occurred at every stage of learning, from apperception to reflection, across the topics of the water cycle, light, the respiratory system, environmental preservation, and cultural heritage; and this implementation positively affected students' engagement, enthusiasm, conceptual understanding, problem-solving ability, and the strengthening of Islamic character traits such as responsibility, care, cooperation, tolerance, and gratitude. This study concludes that a deep learning approach grounded in Islamic values can produce IPAS instruction that is more meaningful, contextual, and reflective, and oriented toward the intellectual, spiritual, and character development of students.